Low molecular weight carbohydrates and abiotic stress tolerance in lentil (Lens culinaris Medikus): a review - Dempsey, Mark; Thavarajah, Dil (Frontiers in Plant Science, 2024)
Lentil (Lens culinaris Medikus) is a nutrient-rich, cool-season food legume that is high in protein, prebiotic carbohydrates, vitamins, and minerals. It is a staple food in many parts of the world, but crop performance is threatened by climate change, where increased temperatures and less predictable precipitation can reduce yield and nutritional quality. One mechanism that many plant species use to mitigate heat and drought stress is the production of disaccharides, oligosaccharides and sugar alcohols, collectively referred to as low molecular weight carbohydrates (LMWCs). Recent evidence indicates that lentil may also employ this mechanism -especially raffinose family oligosaccharides and sugar alcohols -and that these may be suitable targets for genomic-assisted breeding to improve crop tolerance to heat and drought stress. While the genes responsible for LMWC biosynthesis in lentil have not been fully elucidated, single nucleotide polymorphisms and putative genes underlying biosynthesis of LMWCs have been identified. Yet, more work is needed to confirm gene identity, function, and response to abiotic stress. This review i) summarizes the diverse evidence for how LMWCs are utilized to improve abiotic stress tolerance, ii) highlights current knowledge of genes that control LMWC biosynthesis in lentil, and iii) explores how LMWCs can be targeted using diverse genomic resources and markers to accelerate lentil breeding efforts for improved stress tolerance.